Rancangan Model Pemberdayaan Keluarga Pasien terhadap Perawatan Diri (Self Care) Pasien DM Tipe 2 - Intan Kumala Dewi; Blacius Dedi; Lina Safarina; Iin Inayah; Murtiningsih Murtiningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to develop a design model for family empowerment in treating patients with type 2 DM in the working area of ​​EMC Cikarang Hospital. This study uses a qualitative design with an action research approach through two stages of implementation, namely experimental phenomenology and focused group discussions (FGD). The results of this study identified four themes, namely: (1) Family knowledge about Diabetes Militus; (2) the role of the family in caring for DM patients (DM diet management, OAD consumption regulation at home (PMO), DM wound treatment, and monitoring blood sugar levels); (3) the role of the family when they find out that a family member has DM; and (4) Supportive examination of DM patients. In conclusion, family empowerment can change the attitudes and behavior of patients by empowering families who can assist in the form of self-care for DMT2 patients so that the quality of self-care in DMT2 patients becomes better and improves the patient's health status on an ongoing basis. Keywords: Type 2 Diabetes Mellitus, Family Empowerment, Self-Care